A Contribuição do processo ensino-aprendizagem no desenvolvimento humano de discentes do curso técnico integrado em agropecuária do Instituto Federal de Educação Ciência e Tecnologia do Ceará-Campus Umirim - Pereira, Maria Gorete (2015)
This paper carries out an analysis of the contribution of the process of teachinglearning in the development of the students within the Instituto Federal de Educação, Ciência e Tecnologia do Ceará (IFCE) [Federal Institute of Education, Science and Technology of Ceará] Umirim campus. The first part of the paper deals with some concepts related to the theme studied, including constructivist learning and human development in the social interactional perspective, making a relation between human development and the process of learning-teaching. These concepts help to perceive that there exists quite an intrinsic relation between the school environment and the teaching learning process and that this relation contributes significantly to the human development of youth who interact in the school space through the studentprofessor relation. The second part deals with the trajectory of Brazilian professional education and the creation of the Federal Institutes, giving emphasis to the concepts of inclusive education, full time schooling and integrated courses, as well as telling some of the story of the boarding school system in Brazil and how these types of education work within the environment of the IFCE Umirim campus. Although inserted in this context, this institution, specifically, has its origin as an Agricultural School belonging to the Crato campus and only in 2012 does it become a campus tied only to the IFCE, with full time classes and with a boarding school system, attending a clientele of which a great majority comes from the rural area of Vale do Curu and of Aracatiraçu. The third part refers to the characterization of the institution researched: its origin and how the integrated agricultural technical program works, its curricular matrix and a brief analysis of the learning indicators. There is a perception of high indexes of evasion and of school retention in the program researched during the period of three years in which the students remain in the school environment. The fourth and last part refers to the analysis of the field research which was carried out in a qualitative and quantitative way, being that this research integrated semistructured questionnaires and interviews in its context. Finally, the conclusion of the paper focuses on the school which attends to the needs of the worker s child, while one perceives that, although there is attention given to the demands of the needs of this layer of the population, there still lack better results, mainly in the guarantee of permanence with success in learning in the school space and in a special way, in this program, aimed at the qualification of the agricultural workers, an area lacking in professionals in the region of the Vale do Curu and of Aracatiaçu.